STRATEGI MELESTARIKAN KESAKRALAN PURA DI TENGAH PENGEMBANGAN PARIWISATA BUDAYA DI LOMBOK - Budhawati, Ni Putu Sudewi (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2022)
Several temples in Lombok are also ogled as tourist destinations, such as Mayura Temple, Batu Bolong Temple, Linngsar Temple, Suranadi Temple, Narmada Temple, which we ofen see vsited by foreign and local tourist. Thus, management and strategies are need as well as the awerenes of the people to maintain the sacredness and sanctity of the temple. From the background above, there are several problems that are studied, including: 1) What is the role of temples as tourist destinations and their management, 2) How are the strategies for preserving the sacred temples in Lombok. This study uses qualitative research methods, designed to examine socio-religious phenomena. The problems studied use the theory of social change and the theory of religion as a cultural system. The data were obtained using the participation of observation techniques, in-depth interviews, and document studies. The results of this study are as follows : 1) As a tourist destination, to maintain the sanctity and sacredness of the temple, in its management, the temple is managed by the pengempon or guardian, 2) Seeing the many problems related to sacred areas in Lombok, such as the problem of garbage in the area. Sacred places, water pollution, coastal abrasion, it is felt necessary to seek strategies to preserve the sacredness of temples in Lombok, namely as follows : a) Disseminate the teachings of Tri Hita Karana in social life, b) Local governments make regulations regarding the commercial sacredness of temples in the community. Lombok along with the legal provisions in the event of a violation.